Asymmetric polyhedron structured NiSe2@MoSe2 device for use as a supercapacitor. Issue 14 (21st June 2021) - Vidhya, M. Sangeetha; Yuvakkumar, R.; Ravi, G.; Saravanakumar, B.; Velauthapillai, Dhayalan
Abstract : Approaching into the part of redox active sites in charge/discharge material is extremely noteworthy for the progress of high performance of the polyhedron structured NiSe2 @MoSe2 (NMS) hydrolyzed for 18 h as active electrode material. Abstract : The polyhedron-structured NiSe2 @MoSe2 (NMS) were magnificently produced through hydrothermal method, which makes the active electrode very effective in accessing the redox active sites in the charge/discharge process in supercapacitor applications. Systematic studies of the structural and morphological features of the unique polyhedron NMS were performed. Laser Raman spectra reported the vibrational and rotational modes of NMS. NMS exhibited a maximum 1000 F g −1 (138.8 mA h g −1 ) specific capacitance at 1 A g −1 and attained a capacity retention of 77.67% for 5000 stable cycles at 10 A g −1 using 1 M KOH as an electrolyte. The well assembled asymmetric supercapacitor NMS hydrolyzed for 18 h//AC demonstrated an outstanding electrochemical performance with an improved 305 F g −1 specific capacitance attained at 1 A g −1 with a good cycle life of 87.35% and a capacity retention of over 5000 cycles. Herein, the combined contribution of both the Ni and Mo ions offers a richer redox chemistry, which is beneficial to a higher electrochemical activity. The experimental results indicate that the NMS electrode could be used as a high-performance electrode.